The synthesis and characterization of a new vic-dioxime and some of its transition metal complexes - Cukurovali, A; Tas, E (Marcel Dekker Inc, 1998)
The ligand 9,10-bis(hydroxyimino)-4,8,11,15-tetraaza-1,2,17,18-O-dicyclohexylideneoctadecane (LH2) has been synthesized starting from 1,2-O-cyclohexylidene-4-aza-7-aminoheptane, which has been prepared from 1-chloro-2,3-O-cyclohexylidene and dichloroglyoxime. The structures of this vic-dioxime have been determined as the (E,Z)-form according to H-1 NMR and IR data. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II), Ni(II) and UO2(VI). Structures of the ligand and its complexes are proposed based on elemental analyses, IR, UV-VIS, C-13 and H-1 NMR spectra, magnetic susceptibility measurements, and thermogravimetric analyses (TGA).
Keywords: Palladium(Ii); Copper(Ii); Nickel(Ii); Cobalt(Ii); Uranyl(Vi); (E,E)-Dioximes; Platinum(Ii); Mononuclear; Polymers